Narrativas (auto) biográficas de professoras surdas: um olhar para a aprendizagem da docência - Barbosa, Erica Alves (Universidade Federal de São Carlos, 2022)
We start from the assumption that learning how to teach is a continuous process, which occurs throughout life and does not exclusively refer to stagnant training moments, and that the quality of educational processes is, among other factors, related to the teacher and his/her teaching. In the context of deaf education, the "deaf teacher" has a central role in this discussion. Thus, we seek to analyze the teaching learning process of three deaf teachers who work with children in kindergarten and the first years of elementary school. In chapter one, we discuss questions about the field of teacher training, with regard to teaching learning concepts (Mizukami, Marcelo, Vaillant, Tancredi, Imbernón), reflective processes (Zeichner, Knowles, Cole and Presswood, Day), formative experiences (Josso), among others. We associate this with the discussion on aspects related to the specificity and challenges of learning to teach deaf teachers (Lacerda, Martins, Goes and Lodi). The research is based on a qualitative approach, with (auto)biographical sources. The narratives were produced in four phases (initial narratives; deepening; narrative interview and analysis). For analysis, three axes were established: "early times of life, schooling and significant learning"; "professional training, career insertion and significant learning" and "continuous professional development and significant learning". The investigation process allowed us to know the thoughts of the teachers, their life stories, their professional contexts, and offered evidence of their formative experiences. The teachers highlighted: sign language as a foundation in all aspects of their trajectories; the centrality of deaf students in their teaching actions; the school as a locus of professional training; the importance of support from teachers and experienced professionals during the period of initiation into teaching; among other significant experiences for their teaching learning processes. Faced with these considerations, the study indicates the importance that, in the implementation of training processes, in different areas, be taken into account: the specific needs of deaf teachers, the impossibility of separating personal and professional dimensions and the potential of research with sources (auto)biographical for the personalization of these actions.
Biographical (self) narratives of deaf teachers: a look at teaching learning
Keywords: Formação de professores; Professores surdos; Aprendizagem da docência; Narrativas (auto) biográficas; Narrativas surdas; Teacher training; Deaf teachers; Teaching learning; (Auto)biographical narratives; Deaf narratives; CIENCIAS HUMANAS::EDUCACAO